THE EFFECT OF FACILITIES, PRICES, AND WORD OF MOUTH ON VISITORS' SATISFACTION OF GONDANG RESERVOIR TOURISM IN SUGIO DISTRICT - Rizqy Nour Priandini; M. Rizal Nur Irawan; Andi Farouq Hasan (Jurnal Scientia, 2022)
Tourism has an important role for economic growth in an area. In the research that the author examines this time, it is located at the Gondang Reservoir Tourism, Sugio District, where tourism managed by the Tourism Office is related and is included in the regional income of Lamongan Regency. The purpose of this study was to determine the significant effect of facility, price, and word of mouth variables on the satisfaction of visitors to the Gondang reservoir tourism in Sugio District, either partially or simultaneously. This study uses a quantitative method with a sample of 100 visitors to the Gondang Reservoir, Sugio District, using probability sampling and collecting data through questionnaires interviews and observations. While the analytical tools used are validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation, coefficient of determination, t test, F test. The results in this study indicate that the variables of facilities, prices, and word of mouth have a simultaneous effect on visitor satisfaction at Gondang Reservoir tourism in Sugio District where Fcount = 39.455 while Ftable is 2.70 with a significant level of 0.000 <0.05 and simultaneously partial variable facilities, prices, and word of mouth have a positive and significant effect on visitor satisfaction at the Gondang reservoir tourism in Sugio District where tcount for facilities is 2,227 > ttable of 1,984 with a significant level of 0.000 <0.05, the value of tcount for the price variable in get t_count of 4.401 > t_table of 1.984 with a significant level of 0.000 <0.05, the value of t-count, for the word of mouth variable is obtained t_count of 3.238 < t-table of 1.984 with a significant level of 0.005 <0.05. While the price variable is the variable that has the most dominant influence on visitor satisfaction on Gondang Reservoir tourism in Sugio District because this variable has a higher tcount value when compared to other variables.